PENGARUH PENGENDALIAN INTERN TERHADAP KEANDALAN LAPORAN KEUANGAN PADA PT. SAPTA SARI TAMA PALEMBANG - sugiharto sugiharto; Salman Salman (Jurnal RATRI (Riset Akuntansi Tridinanti), 2021)
This research aims to see the effect of the implementation of internal control on the realiability of financial reporting. The financial reporting show indications of receivables that are not in line with expectations and the occurrence of excess or shortage of stock. This reporting is closely related to the implementation of internal control that can achieve the purpose of its implementation, namely the realiability of financial reporting. The population and sample in this research were 40 employees, all of which were used as a population. This research used exploratory and causality and the formulation of associative problems using questionnaires. Based on the results of the research, internal control affects the realiability of financial reporting. The conclusion of this research states that the hypothesis which states that internal control affects the realiability of financial reporting is acceptable.